2021
DOI: 10.1002/cncr.33957
|View full text |Cite
|
Sign up to set email alerts
|

Risk of suicide among individuals with a history of childhood cancer

Abstract: BACKGROUND: Previous studies have described suicidal ideation among survivors of childhood cancer, but small numbers of events limit the understanding of suicide risk. The objectives of this study were to assess whether childhood cancer survivors are at increased risk of suicide in comparison with the general population and to determine risk factors associated with risk in a population-based cohort. METHODS: First primary malignancies among individuals aged 0 to 19 years from 1975 to 2016 were identified from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 39 publications
(92 reference statements)
1
9
0
Order By: Relevance
“…Results of risk of bias assessment using the Joanna Briggs Institute critical appraisal tools (eTable 17 in Supplement 1) showed that although studies overall were not at significant risk of bias, a proportion used normative population data rather than matched controls . Publication bias, outlier assessment, and leave-one-out analysis was also performed (eFigures 6-25 in Supplement 1).…”
Section: Resultssupporting
confidence: 67%
See 4 more Smart Citations
“…Results of risk of bias assessment using the Joanna Briggs Institute critical appraisal tools (eTable 17 in Supplement 1) showed that although studies overall were not at significant risk of bias, a proportion used normative population data rather than matched controls . Publication bias, outlier assessment, and leave-one-out analysis was also performed (eFigures 6-25 in Supplement 1).…”
Section: Resultssupporting
confidence: 67%
“…From 7319 results (Figure 1), we included a total of 52 studies reporting psychiatric disorders and psychological symptoms of depression, anxiety, psychotic disorders (including schizophrenia), and suicide mortality in CYACs compared with controls without cancer (eTable 2 in Supplement 1). Most studies recruited healthy, age-matched comparators as a control group, whereas 13 studies recruited siblings and 3 studies recruited parents or caregivers of patients with cancer.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations